Features of Education in Canada - Abdukhalikovna, Mamadkulova Kamila; Jasmina, Ziyadullayeva (Research Parks Publishing LLC, 2023)
The report discusses the features of primary, secondary, higher education in Canada. Canada is a leader in the field of high technologies, aerospace industry and microelectronics. The strength of Canadian higher education is the close connection between science and practice.